Sanghuangporus vaninii fruit body polysaccharide alleviates hyperglycemia and hyperlipidemia via modulating intestinal microflora in type 2 diabetic mice - Huang, Zi-Rui; Huang, Qi-Zhen; Chen, Ke-Wen; Huang, Zi-Feng; Liu, Yun; Jia, Rui-Bo; Liu, Bin (Frontiers in Nutrition, 2022)
The disease of type 2 diabetes mellitus (T2DM) is principally induced by insufficient insulin secretion and insulin resistance. In the current study, Sanghuangporus vaninii fruit body polysaccharide (SVP) was prepared and structurally characterized. It was shown that the yield of SVP was 1.91%, and SVP mainly contains small molecular weight polysaccharides. Afterward, the hypoglycemic and hypolipidemic effects and the potential mechanism of SVP in T2DM mice were investigated. The results exhibited oral SVP could reverse the body weight loss, high levels of blood glucose, insulin resistance, hyperlipidemia, and inflammation in T2DM mice. Oral SVP increased fecal short-chain fatty acids (SCFAs) concentrations of T2DM mice. Additionally, 16S rRNA sequencing analysis illustrated that SVP can modulate the structure and function of intestinal microflora in T2DM mice, indicating as decreasing the levels of Firmicutes/Bacteroidetes, Flavonifractor, Odoribacter, and increasing the levels of Weissella, Alloprevotella, and Dubosiella. Additionally, the levels of predicted metabolic functions of Citrate cycle, GABAergic synapse, Insulin signaling pathway were increased, and those of Purine metabolism, Taurine and hypotaurine metabolism, and Starch and sucrose metabolism were decreased in intestinal microflora after SVP treatment. These findings demonstrate that SVP could potentially play hypoglycemic and hypolipidemic effects by regulating gut microflora and be a promising nutraceutical for ameliorating T2DM.